Effect of the Temperature and Grain Direction on the Stress Relaxation Behavior of Pcm-Impregnated and Nonimpregnated Wood Under Tensile and Bending Stresses - Garcia-Herrera, C; Vasco-Calle, D; Utrera-Soto, A; Jonathan Jesus-Cofre, T; Fuentes-Sepulveda, R (Springer Science and Business Media Deutschland GmbH, 2023)
Due to its anatomical properties, wood is an anisotropic, porous, and heterogeneous material with constituent cells of varying types and shapes. The time-dependent mechanical response of wood is of notable interest in structural applications, especially the viscoelastic response. This work characterized the viscoelastic response of Pinus radiata impregnated with a paraffinic phase change material (PCM; technical grade octadecane), thereby considering the longitudinal, radial, and tangential log directions. In addition, the effect of the temperature on the viscoelastic response was examined, evaluating the PCM in the solid (15 ∘C) and liquid (35 ∘C) states. The elastic moduli of all tested wood specimens indicated similar trends; the magnitude was the largest along the longitudinal direction, followed by the tangential and radial directions. In the solid PCM phase, the stress relaxation decreased along the longitudinal direction regarding liquid-phase PCM. Conversely, greater relaxation responses were observed along the radial and tangential directions in the presence of solid-phase PCM compared to a liquid-phase-impregnated sample. Finally, a nonlinear response was observed along the tangential direction during the relaxation tests, depending on the strain reached. © 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.